Analysis of Power Consumption in the drilling of Nano SiC reinforced Aluminium matrix composites. Issue 1 (October 2020) - Kalyan Chakravarthy, V. V.; Rajmohan, T.
Abstract: Nanoceramic particles reinforced Metal Matrix Composites (MMNC) have gained immense attention from both the scientific and industrial community. The employment of these advanced class materials in the industries has given many advantages. These Nanocomposites are very difficult to machine, and the number of holes is to be drilled on their surface for many applications as drilling is considered as one of the significant applications in the industry. The researchers and industrial experts are striving very hard to attain green manufacturing techniques in drilling, which creates less impact on the environment and consume lower power. The main aim of current research is to analyse the power consumption in the drilling of Nano silicon carbide (SiC) reinforced Aluminium (Al) matrix composite under various machining conditions, cutting speeds, feed rates. For this purpose, a series of experiments have been planned using Taguchi's L18 orthogonal array. The drilling tests were performed using a vertical machining centre (VMC) which is controlled by computer numeric control (CNC) employing carbide drills of 10mm dia with cutting point angles of 90°, 118° and 135°. The machining operation is performed under Dry cutting and Cryogenic cutting condition. On successful completion of the experiments, the surface morphology is studied using Field Emission Scanning Electron Microscopy (FESEM).